Forest ecosystem restoration in the Ore Mountains: A review of silvicultural measures addressing environmental degradation - Veronika Hammerová; Stanislav Vacek; Zdeněk Vacek; Jakub Černý; Jan Cukor; Josef Gallo; Michal Kuběnka (Journal of Forest Science)
The forest dynamics of the Ore Mountains (Krušné hory), Czech Republic, reveal a historical decline of natural mixed forests, especially those dominated by the Hercynian mixture and European beech (Fagus sylvatica L.), due to the expansion of metallurgy and glassmaking in the 15th century. This led to large-scale reforestation with Norway spruce [Picea abies (L.) Karst.], resulting in single-layered monocultures. Although these monocultures provided valuable timber, they proved highly susceptible to both biotic and abiotic stressors. Throughout the 20th century, the stability of these forests further deteriorated due to air pollution (notably SO2 emissions), the unsuitable selection of substitute species, and the proliferation of pathogens. The cumulative impact of these disturbances caused soil acidification, degradation, and weed encroachment, severely limiting the regenerative capacity of forest ecosystems in this region. This article presents model examples of species composition shifts, spatial structure changes, and evolving management practices in the Ore Mountains. It discusses strategies for establishing diverse and resilient stands that align with long-term forest planning goals. These approaches aim to maintain both productive and ecological functions of forests under changing environmental conditions while minimising restoration costs. Importantly, forest management and conversion strategies must also account for economic optimisation, ensuring that ecological goals are met in a financially viable manner. The strategies and case studies presented here offer promising, albeit preliminary, directions for future forest management. Their broader application will require further refinement and long-term experimental validation to ensure sustainability in both ecological and economic terms.